The Role of the Principal in Improving Educator Performance in Islamic Schools - Halima, Raden Ayu; Ali, Mohamad; Wachidi, Wachidi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine in depth the various strategic roles of school principals in the context of Islamic schools, especially in improving the quality of educator performance and strengthening educational governance based on Islamic values. The method used in this study is a literature review, by examining various recent scientific journals in the period 2019–2024. The results of the study show that school principals have various important roles, namely as managers, innovators, communicators, academic supervisors, motivators, and role models. In their role as managers, school principals are responsible for teacher development planning, monitoring, and periodic evaluation of educator performance. As innovators, school principals encourage teachers to innovate in learning and be adaptive to new technologies and methods.The role of communicator is also important, where the principal is expected to build effective and assertive communication with teachers in order to foster trust and loyalty. In terms of academic supervision, the principal functions as a mentor in implementing effective and reflective learning. Internal challenges such as limited funds and teacher motivation, as well as the influence of foundation management, are obstacles that need to be overcome with collaborative solutions and strengthening synergy between the principal, teachers, and the foundation. Meanwhile, external challenges in the form of competition with public schools and the globalization of education require adaptive and innovative strategies. This study recommends the use of technology, the formation of a professional network of Islamic teachers, and reward and punishment-based evaluation as strategic approaches in improving the quality of Islamic education. With visionary and value-based leadership, the principal plays a central role in making Islamic schools superior and competitive institutions.